Analysis of the Acceptance of Sharia Bond Funds to the Income Bank of Muamalat Indonesia Tbk. - Heriyati Chrisna (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this research is to analyze the process of issuance of sharia bonds at Bank Muamalat Indonesia Tbk and to know how big the contribution of sharia bonds funds against the income of the Bank Transactions Indonesia, Tbk. The object of the study was conducted in the Bank Muamalat Indonesia, Tbk. Type of this research uses the descriptive research to achieve the goal of this research i.e. to provide a clear picture of the problems examined, data source that is used is a secondary data and the data is qualitative research, and the author uses the technique of observation and documentation, and bibliographical technique (library research)for data collection techniques. The results of research, the author basically uses the principle of sharia bonds like conventional bonds with the essential difference among others in the form of the use of the concept of the reward and for the result sharing is as a replacement of the interest. The income of fund management by a bank as the mudharib for the period 2010 until 2014 increased, but it decreased in 2015 amount of Rp 265.503.473 or 5.09 cents%. Result sharing of Sharia Bonds that obtained from the sukuk issuance of the subordination of the Bank Muamalat for the year 2008 was Rp 314.000.000.000 with return period (tenor) ten years, the results sharing obtained from 2010 to 2015 was Rp. 982.703.166.